Agricultural Family School: reflections about contributions to rural communities - Adriana Rodrigues da Silva; Aline Weber Sulzbacher (Universidade Federal do Norte do Tocantins, 2020)
In this article, we aim to analyze the field education project of the Escola Família Agrícola in the city of Veredinha (MG) and, from it, discuss the contributions to the subjects that make up the community; and, to contribute to the discussion about the role of geography teaching in rural education projects. The methodological procedures involve the realization of a specialization course monograph, including research and bibliographical study, document analysis and systematic observation. We indicate as contributions the capacity of mobilization and social organization of the farmers and the pedagogical alternation, which reverberate in the educational spaces and are consolidated with young people active in the region. EFAV contributes to the production of territories of resistance, with significant changes in regional dynamics. We conclude by pointing out that the EFAV was created to guarantee access to secondary and technical education for young people in the countryside, but it has advanced in a pedagogical and political proposal that meets the interests of the subjects in the countryside. To this end, it involved popular mobilization and also the articulation of different social organizations. The school itself mobilized educational and political processes that mobilized and raised awareness among communities and farmers.